2000
DOI: 10.1007/s002590000333
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of radioiodine treatment in the management of differentiated thyroid cancer in Germany

Abstract: This prospective, observational study of a cohort of thyroid cancer patients in Germany focusses on the "real-world" practice in the management of thyroid cancer patients. This report includes data from 2376 patients with primary differentiated thyroid carcinoma first diagnosed in the year 1996. The study reveals considerable differences in actual practice concerning surgery and radioiodine treatment. The results indicate that consensus is lacking with respect to the multimodality treatment approach for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…None of these series included patients prepared with rhTSH stimulation. Similar to our study, a dose-response relationship was seen in 2 of the studies (11,23), demonstrating an increased risk of SSEs at administered activities greater than 11,100 MBq (300 mCi). The slightly higher incidence of side effects in our series is likely related to improved documentation associated with the standardized data collection forms completed by a trained thyroid cancer nurse or clinicians with an interest in potential RRA side effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…None of these series included patients prepared with rhTSH stimulation. Similar to our study, a dose-response relationship was seen in 2 of the studies (11,23), demonstrating an increased risk of SSEs at administered activities greater than 11,100 MBq (300 mCi). The slightly higher incidence of side effects in our series is likely related to improved documentation associated with the standardized data collection forms completed by a trained thyroid cancer nurse or clinicians with an interest in potential RRA side effects.…”
Section: Discussionsupporting
confidence: 89%
“…Only 4 studies (Table 3) (11,12,22,23) that would be comparable to our series have examined long-term SSEs with single-dose RAI. These studies have reported salivary gland toxicity rates in the range of 6.7%233% in patients prepared with traditional THW.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies reported a higher number of cumulative treatments were associated with increased risk of salivary gland side effects from 131 I therapy [8,19,24,25,31]. In single-dose radioiodine therapy, the risk of persistent salivary gland side effects is increased at administered doses of more than 11,100 MBq (300 mCi) [32,33]. .…”
Section: Early and Late Sialadenitismentioning
confidence: 99%
“…Normal technetium-99m pertechnetate uptake is shown in both parotid and submandibular glands and normal clearance of accumulated technetium-99m pertechnetate Persistent salivary gland side effects developed in a few patients with ablation doses of radioiodine. Acute salivary gland side effects developed in 6.9-33% of patients with single dose 131 I ablation [32][33][34][35]. They demonstrated a dose-response relationship between administered amount of radioiodine and salivary gland side effects.…”
Section: Early and Late Sialadenitismentioning
confidence: 99%
“…In European countries, 2.6% of patients in a Greek center (Tzavara et al 1999) employed EXT. In a German study of 2376 patients with differentiated thyroid cancer (DTC), 12% (19/162) of patients with advanced stage PTC (T1-3N1M0, American Joint Committee on Cancer (AJCC) 5th edition) received EXT (Hoelzer et al 2000).…”
Section: Introductionmentioning
confidence: 99%